2015
DOI: 10.3390/buildings5020536
|View full text |Cite
|
Sign up to set email alerts
|

Using Life Cycle Assessment to Inform Decision-Making for Sustainable Buildings

Abstract: Because the student residences of the Vrije Universiteit Brussel built in 1973 are not adapted to current comfort standards, the university decided to construct new accommodation facilities at the border of the campus. However, besides demolition, there was no strategy on how to deal with the existing ones. In the search for a more sustainable strategy, the university's administration assigned the TRANSFORM research team to define various design strategies and to assess the long-term environmental consequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 28 publications
(49 reference statements)
0
22
0
Order By: Relevance
“…As discussed by several authors and in detail by [3] the main component of concrete is cement, which releases significant quantities of carbon dioxide (CO 2 ) into the atmosphere [4]. In other words, the production of concrete has a notable impact on the environment, and environmental problems are known to be quite serious in the construction industry [5][6][7][8]). …”
Section: Introductionmentioning
confidence: 99%
“…As discussed by several authors and in detail by [3] the main component of concrete is cement, which releases significant quantities of carbon dioxide (CO 2 ) into the atmosphere [4]. In other words, the production of concrete has a notable impact on the environment, and environmental problems are known to be quite serious in the construction industry [5][6][7][8]). …”
Section: Introductionmentioning
confidence: 99%
“…DfC is a design and construction strategy based on the principle that the requirements and aspirations of society and users on our built environment will always change [15]. These changing requirements are, among others, changing standards, family composition, changing patterns of life and an evolving work environment [16]. The aim is to make a building easily adaptable during its lifetime and, in this study, to design dwellings to become life-cycle houses that truly support changes.…”
Section: Design For Changementioning
confidence: 99%
“…According to Kirchherr et al [17], who identified 114 different CE definitions, a circular economy can be defined as "an economic system that is based on business models which replace the 'endof-life' concept with reducing, alternatively reusing, recycling and recovering materials [...] with the aim to accomplish sustainable development [...]." In this regard, previous studies have shown that applying a design that anticipates the whole life cycle of a building has the potential to decrease its environmental impact [16] because integrating adaptability promotes less material consumption and less demolition waste [18], as buildings are reconfigured instead of demolished and rebuilt. Moreover, a house that is initially designed to adapt to changing lifestyles is expected to have lower adaptation costs [19].…”
Section: Design For Changementioning
confidence: 99%
“…For the fifth phase of the assignment, the assessment, the design guidelines for 'design for change' on the element level developed by the Flemish agency for waste management (OVAM) based on Vandenbroucke [7] were used. Nine criteria are differentiated in three aspects: interface, which focuses on the interaction between components, holds the criteria 'reversibility', 'simplicity', and 'speed'; components, which focuses on the features of the parts, holds the criteria 'compatibility', 'durability', and 'manageability'; and composition, which focuses on the whole, holds the criteria 'independence', 'pace-layering', and 'prefabrication'.…”
Section: Framework Of Evaluation Criteria For Design For Changementioning
confidence: 99%